1997
DOI: 10.1021/ja964434z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Control of Surface Potential and Wetting of Solids with Chemisorbed Multifunctional Ligands

Abstract: Homogeneously mixed molecular assemblies of defined stoichiometry were created by adsorption of asymmetric, trifunctional ligands on gold and CuInSe2 (CISe). The ligands rely on cyclic disulfide groups for binding to the substrate and can in addition possess two different substituents, one polar substituent (p-cyanobenzoyl or anisoyl) and one long-chain, aliphatic residue (palmitoyl). Because the substituents are covalently connected, no phase segregation will occur upon surface binding. Adsorption of these li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(126 citation statements)
references
References 93 publications
7
119
0
Order By: Relevance
“…A combination of CPD and saturated-SPV measurements was used in recent years by Cahen et al for deducing the systematic effects of various organic ligands to semiconductor surfaces on the bandbending and surface dipole at CuInSe 2 [50,51,54], CdTe [50,51,55,56], CdSe [52], GaAs [53], and Si [57] surfaces. Organic ligands are an attractive alternative to the inorganic treatments usually used for surface control.…”
Section: Surface Dipolementioning
confidence: 99%
See 1 more Smart Citation
“…A combination of CPD and saturated-SPV measurements was used in recent years by Cahen et al for deducing the systematic effects of various organic ligands to semiconductor surfaces on the bandbending and surface dipole at CuInSe 2 [50,51,54], CdTe [50,51,55,56], CdSe [52], GaAs [53], and Si [57] surfaces. Organic ligands are an attractive alternative to the inorganic treatments usually used for surface control.…”
Section: Surface Dipolementioning
confidence: 99%
“…Organic ligands are an attractive alternative to the inorganic treatments usually used for surface control. This is because organic ligands feature structural versatility and¯exibility, may be designed to incorporate several properties simultaneously, and potentially allow systematic modi®cations of one speci®c property independent of the others [54,56].…”
Section: Surface Dipolementioning
confidence: 99%
“…[13,14] We [3,64,109,110] and others [63,[111][112][113] have shown that adsorbing molecules with intrinsic dipoles and/or polar bonding to a solid can change the barrier height for transport in an MS/MIS junction. The theoretical potential drop, C I , can be calculated from: [114,115] . C I and m ?…”
Section: Dipolar Effects Of the Molecular Monolayermentioning
confidence: 99%
“…m ? is composed of three contributions, [113][114][115] which we illustrate here for SiÀalkyl systems: the intrinsic molecular dipole, m mol ; the SiÀC bond dipole, m Si-C and the ''pillow effect'', m Me/Hg .…”
Section: Dipolar Effects Of the Molecular Monolayermentioning
confidence: 99%
See 1 more Smart Citation